2016
DOI: 10.1038/srep38275
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of TREM-1 blockade and single nucleotide variants in experimental renal injury and kidney transplantation

Abstract: Renal ischemia reperfusion (IR)-injury induces activation of innate immune response which sustains renal injury and contributes to the development of delayed graft function (DGF). Triggering receptor expressed on myeloid cells-1 (TREM-1) is a pro-inflammatory evolutionary conserved pattern recognition receptor expressed on a variety of innate immune cells. TREM-1 expression increases following acute and chronic renal injury. However, the function of TREM-1 in renal IR is still unclear. Here, we investigated ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 54 publications
1
25
1
Order By: Relevance
“…Interestingly, however, TREM-1 was also shown to mediate an inhibitory effect on necroptosis and pyroptosis in neonatal lung tissue, as suggested in previous work by Syed et al (145). In our hands, in the early phase of renal IRI, TREM-1 modulation did not affect tubular damage or renal function (146). However, we did find that mice lacking TREM-1 displayed maladaptive repair characterized by persistent tubular damage, inflammation, fibrosis, and mitochondrial dysfunction-induced TEC senescence when exposed to renal IRI (52).…”
Section: Trem-1supporting
confidence: 84%
“…Interestingly, however, TREM-1 was also shown to mediate an inhibitory effect on necroptosis and pyroptosis in neonatal lung tissue, as suggested in previous work by Syed et al (145). In our hands, in the early phase of renal IRI, TREM-1 modulation did not affect tubular damage or renal function (146). However, we did find that mice lacking TREM-1 displayed maladaptive repair characterized by persistent tubular damage, inflammation, fibrosis, and mitochondrial dysfunction-induced TEC senescence when exposed to renal IRI (52).…”
Section: Trem-1supporting
confidence: 84%
“…sTREM‐1 has been studied in sepsis and in other systemic conditions. Previous studies have observed that acute and chronic kidney injury and hemodialysis activate innate immunity and thus TREM‐1 expression . According to the authors’ knowledge there are only a few studies on the usefulness of TREM‐1 as an oral inflammatory biomarker .…”
Section: Discussionmentioning
confidence: 99%
“…This could be artificially elevated because of conditions present in vivo that we cannot reproduce artificially, such as involvement of other biological cofactors, temperature, and molecular stability. The TREM-1 antagonists function primarily as decoy receptors and to prevent receptor dimerization (21,30). Additionally, Sigalov et al have developed a ligand-independent inhibitor of TREM-1 (31,32).…”
Section: Discussionmentioning
confidence: 99%